1968
DOI: 10.1172/jci105726
|View full text |Cite
|
Sign up to set email alerts
|

The nature of human serum insulin-like activity (ILA): characterization of ILA in serum and serum fractions obtained by acid-ethanol extraction and adsorption chromatography

Abstract: AB STRACT Studies were undertaken in an attempt to clarify the apparent heterogeneous nature of human serum insulin-like activity. Methods of preparative zone electrophoresis on Pevikon, acid-ethanol extraction of trichloroacetic acid serum protein precipitates, adsorption chromatography on DEAE-cellulose and Dowex 50, gel filtration chromatography, and insulin antiserum immunoreactivity were used. The results establish the presence of a substance in serum with in vitro biological properties similar to insuln … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

1968
1968
1978
1978

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 62 publications
1
10
2
Order By: Relevance
“…Gel-filtration of fraction S (soluble in acidethanol) on Sephadex G-100 at neutral pH yielded an elution pattern of nonsuppressible ILA similar to that found by other authors working with Sephadex at neutral pH ( 18,20). Thus, Cameron, Boyns, Jarrett, and Keen (17) found that ILA of a trichloroacetic acid extract of human plasma eluted from Sephadex G-200 at neutral pH over a wide range.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Gel-filtration of fraction S (soluble in acidethanol) on Sephadex G-100 at neutral pH yielded an elution pattern of nonsuppressible ILA similar to that found by other authors working with Sephadex at neutral pH ( 18,20). Thus, Cameron, Boyns, Jarrett, and Keen (17) found that ILA of a trichloroacetic acid extract of human plasma eluted from Sephadex G-200 at neutral pH over a wide range.…”
Section: Discussionsupporting
confidence: 69%
“…(18) that "bound insulin" and nonsuppressible ILA soluble in acid-ethanol (fraction S) are the same. The controversal estimates of the molecular size clearly are due to the different conditions chosen for Sephadex chromatography.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations